Linguistic purism and language criticism in English - Busse, Beatrix; Möhlig-Falke, Ruth; Vit, Bryan (Handbuch europäische Sprachkritik online, 2018)
Linguistic purism refers to an activity which aims at cleansing a language from unwanted influences. However, what counts as an ‘unwanted influence’ usually rests on certain social ideals that are not necessarily shared by all members of a society. These ideals may be oriented towards a nostalgic conception of the past, towards certain ethnographic varieties, or towards the language usage of a conceived social elite. This article gives an overview of different language-purifying attempts made with respect to British English in the course of its history. In comparison with other languages, it is remarkable that purifying efforts have never exerted any larger or longer-lasting influence on the English language, despite or because of the diverse situations of language contact that it was involved in.
Gesehen am 23.05.2023